Effect of Folic Acid by injection and supplementary on growth and puberty of Karadi male lambs. - Karim, Ismael Othman; Omar, Chowman Aladdin (Kurdistan Journal of Applied Research, 2021)
The present study is carried out to study the effect of Folic Acid (FA) by injection and supplementary on animal body weight gain, Testes volume before slaughtering, Testes volume after slaughtering, Testosterone concentration in blood, and FA concentration in blood. Twenty-five (25) Karadi male lambs five months aged and the average weight was 24.54 ±1.92 kg were used in this experiment. The animals weighed after three months of treatment to get animal increased live weight, The testes measured after one, two, and three months of treatment to calculate testes volume, testosterone, and FA concentration level in the blood were taken after one, two, and three months of treatment. The present study demonstrated that animal body weight, animal body weight gain, and total body weight gain significantly not increased (p>0.05). Testicular length, and testicular circumference not increased (p>0.05) after 1st, 2nd, and 3rd months after treatment, and after slaughtering. However, testicular high increased (p<0.05) after each month of treatment and slaughtering. Testosterone concentration in the blood significantly not different (p>0.05) reported between treatments after the 1st, 2nd, and 3rd months of treatment. FA concentration in the blood significantly increased (p<0.05) when used 3 and 6 mg FA by injection compared to control after 1st and 2nd months of treatment. However, blood FA concentration increased (p<0.05) when used FA 6mg/ml as an injection after the 2nd month of treatment compared to control. While using FA by supplementation and injection significantly (p>0.05) on the diameter and circumference of seminiferous tubules, germ cells thickness, and lumen diameters.